SECURITY, DISINFORMATION AND ARTIFICIAL INTELLIGENCE: A Security Perspective on Artificial Intelligence in our Information Landscape. - Butler, Dawn (Parliamentarian, 2025)
The article focuses on the security implications of artificial intelligence in the modern information landscape. Topics include the role of AI in spreading disinformation, the risks posed by deepfake technology especially in targeting women and the need for regulatory measures to ensure artificial intelligence (AI) is used responsibly.